2003
DOI: 10.1037/1524-9220.4.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity ideology among Russian and U.S. young men and women and its relationships to unhealthy lifestyles habits among young Russian men.

Abstract: One aim of this study was to further investigate the empirical support for the social constructionist perspective on gender roles. A 2nd aim was to explore the relationship between Russian men's endorsement of traditional masculinity ideology and their engagement in behaviors that may put their health at risk. Russian respondents endorsed traditional masculinity ideology, developed for a U.S. sample, to a higher degree than did their American counterparts. Overall, women endorsed a less traditional perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 22 publications
3
52
1
2
Order By: Relevance
“…But because communists were among the leaders in promoting gender equality (Richmond, 1996), we might expect few gender differences in friendship patterns in Russia than in the United States. However, recent research suggests that the communist rhetoric may have largely gone ignored: Russian men cling to traditional gender beliefs more than American men do (Levant et al, 2003), and they show greater support for a double-standard in sexual relationships (Sprecher & Hatfield, 1996). We therefore suspect that gender differences in friendship may actually be accentuated in Russia relative to the United States.…”
Section: Gender and Friendshipmentioning
confidence: 87%
“…But because communists were among the leaders in promoting gender equality (Richmond, 1996), we might expect few gender differences in friendship patterns in Russia than in the United States. However, recent research suggests that the communist rhetoric may have largely gone ignored: Russian men cling to traditional gender beliefs more than American men do (Levant et al, 2003), and they show greater support for a double-standard in sexual relationships (Sprecher & Hatfield, 1996). We therefore suspect that gender differences in friendship may actually be accentuated in Russia relative to the United States.…”
Section: Gender and Friendshipmentioning
confidence: 87%
“…Lithuania, Russia, Slovakia, Slovenia and Poland (Olson, et al, 2007) and for attitudes 10 toward women among students from Croatia, Slovenia and the USA, (Frieze, et al, 2003) as 11 well as among young men and women from the Russia and USA (Levant, et al, 2003). 12 When it comes to ambivalent attitudes to men, the picture is more complex and 13 depends on the type of attitudes.…”
mentioning
confidence: 99%
“…The few cross-national studies which include CEE countries and use gender attitude measures (Frieze et al 2003, Levant et al 2003, Shafiro et al 2003 have demonstrated their greater gender conservatism as compared to Western nations. However, such studies largely neglect consideration of PL.…”
mentioning
confidence: 99%
“…This was shown in 14 countries drawn from across North and South America, Africa, Europe and Asia (except for Malaysia and Pakistan, Williams and Best 1990) as well as for CEE in terms of overall gender equality (Olson et al 2007) and attitudes towards women (Frieze et al 2003, Levant et al 2003.…”
mentioning
confidence: 99%